PERSEPSI PELAKU USAHATANI TERHADAP KEBIJAKAN DAN PROGRAM INVESTASI PUBLIK DI SEKTOR PERTANIAN - Widyastutik; Hotsawadi; Setyawati, Dewi; Amaliah, Syarifah; Hermawan, Iwan (RISALAH KEBIJAKAN PERTANIAN DAN LINGKUNGAN Rumusan Kajian Strategis Bidang Pertanian dan Lingkungan, 2025)
Public investment in the agricultural sector is expected to increase production and farmer welfare. This study aims to analyze business actors' perceptions of public investment policies and programs in the agricultural sector. The sample of respondents was 300 farmers who cultivate rice, corn, soybeans, vegetables, cocoa and palm oil commodities in five districts (Subang, Indramayu, Pacitan, North Lombok and North Luwuk). Farmers' perceptions based on Importance Performance Analysis (IPA) analysis show that the performance of production facilities, agricultural machinery and infrastructure in general must be maintained. Meanwhile, for other factors such as human resources, research and development, use of technology, financing, government policies, government and institutional assistance, facilitation and partnerships, farmer respondents have levels of interest and also performance perceptions that vary greatly between sample locations and commodity types.  As an effort to optimize public investment, assistance activities by ministries, institutions, the private sector and universities for farmers are very necessary.